Analysis of the determinants of public capital investments on agricultural water infrastructure in Eswatini - Nhlengethwa, Sibusiso; Matchaya, Greenwell C.; Greffiths, Ikhothatseng Jacob; Fakudze, Bhekiwe (Wiley, 2021)
Infrastructure investment is one of the main preconditions for enabling developing countries to accelerate or sustain the pace of their development and achieve the Sustainable Development Goals. This paper examines the determinants of agricultural water infrastructure investments in the Kingdom of Eswatini. Using annual data (time series); Pearson Pair-wise Correlation, Unit-root tests and OLS regression techniques are applied to determine the relationship between public infrastructure investment and factors that influence public investments. Agricultural water infrastructure investment is found to be positively correlated to GDP, Sugar export income and FDI into agriculture. Past economic growth and sugar export values are the two critical determinants of agricultural water infrastructure investments in Eswatini. It can be safely construed that higher incomes as well as terms of trade for sugar, can improve spending on agriculture water investments. This is important because an increase in investments in water infrastructure may then help spur economic growth.